2017
DOI: 10.1016/j.molmet.2017.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Adipocyte lipid synthesis coupled to neuronal control of thermogenic programming

Abstract: BackgroundThe de novo biosynthesis of fatty acids (DNL) through fatty acid synthase (FASN) in adipocytes is exquisitely regulated by nutrients, hormones, fasting, and obesity in mice and humans. However, the functions of DNL in adipocyte biology and in the regulation of systemic glucose homeostasis are not fully understood.Methods & resultsHere we show adipocyte DNL controls crosstalk to localized sympathetic neurons that mediate expansion of beige/brite adipocytes within inguinal white adipose tissue (iWAT). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
87
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(94 citation statements)
references
References 69 publications
7
87
0
Order By: Relevance
“…It is also conceivable that a permissive amount of insulin signaling may be sufficient for the full biological effects of insulin. This concept is supported by literature showing a lack of linearity between insulin signaling and insulin effects on glucose transport (Gonzalez et al, 2011; Kajno et al, 2015; Tan et al, 2015) and other biological processes (Guilherme et al, 2017; Kajno et al, 2015). Consistent with this, we observe impaired insulin-stimulated Akt T308 phosphorylation in WAT of HFD-fed AdChREBP KO vs. ChREBP fl/fl mice (Fig 4N, grey vs. black bars) without impairments in insulin-stimulated glucose transport in adipocytes isolated from HFD-fed AdChREBP KO mice (Fig S5D, white vs. black bars).…”
Section: Discussionmentioning
confidence: 59%
“…It is also conceivable that a permissive amount of insulin signaling may be sufficient for the full biological effects of insulin. This concept is supported by literature showing a lack of linearity between insulin signaling and insulin effects on glucose transport (Gonzalez et al, 2011; Kajno et al, 2015; Tan et al, 2015) and other biological processes (Guilherme et al, 2017; Kajno et al, 2015). Consistent with this, we observe impaired insulin-stimulated Akt T308 phosphorylation in WAT of HFD-fed AdChREBP KO vs. ChREBP fl/fl mice (Fig 4N, grey vs. black bars) without impairments in insulin-stimulated glucose transport in adipocytes isolated from HFD-fed AdChREBP KO mice (Fig S5D, white vs. black bars).…”
Section: Discussionmentioning
confidence: 59%
“…Fatty acid synthase deletion in adipose tissue can prevent insulin resistance in mice, possibly through generation of bio-active lipids 136 , although other work suggest beneficial lipids are actually derived from DNL 137,138 . DNL may regulate adipocyte biology through the multiple signaling pathways that it controls (Figure 5, within rectangle at right), including the potential to regulate neuronal innervation and sympathetic nerve activity within adipose tissue 139 . Acetyl CoA is a substrate for protein acetylation reactions, most notably acetylation of histones that modulate their DNA binding activities to regulate transcription 140144 .…”
Section: Cellular and Molecular Causes Of Impaired Insulin Responsivementioning
confidence: 99%
“…Yet the etiology of insulin resistance is complicated and multifaceted, involving both cell autonomous mechanisms and inter-organ communications (Figure 2). Careful investigation has revealed that many disruptions causing systemic insulin resistance actually occur downstream or independent of insulin signaling to the protein kinase Akt 69,122,126,127,130,139 , even though the Akt pathway is often also effected. We are still unable to precisely define the mechanisms that cause most of these basic disruptions, partly because there is considerable disagreement among the many laboratories in the field.…”
Section: Conclusion and Perspectives For Future Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, adipocyte DNL perturbation not only modulates the thermogenic programming of iWAT, but also whole-body metabolism. Adipocyte DNL may produce bioactive lipids that alters adipose tissue functions 18 , energy balance and systemic metabolism 3,19,20 . This pathway is also a rich source of metabolites such as acetyl-CoA, malonyl-CoA, palmitate and lipid products, all known to control diverse cellular processes 2,21,22 .…”
Section: Introductionmentioning
confidence: 99%